النبر والتنغيم وتطبيقاتهما في اللغة العربية : دراسة صوتية دلالية في الخطاب الشفهي - Basiron Abdullah (Kuliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2008)
Stress and intonation are considered as important subjects of phonetics, because they are related to performance of speech in a language. Performance is a sole feature of a language and the language, in fact, is the spoken voices and writing is an attempt to exemplifying the spoken voices. Therefore, this research aims to describe one of the phonetics' branches. It examines the phenomena of stresses and intonations in Arabic language. In this respect, the study will highlight the relevant characteristics relating to both of them. Further, this research will study the actual phenomena relating to these two matters in the standardized spoken Arabic in both speaking and reading. This research uses three methods in order to study this topic; they are descriptive, inductive and analytic methods.